Tahap pengamalan pengurusan keselamatan dalam industri kecil dan sederhana - Aspar, Mohd. Hanip (2007)
This research is to determine the relationship between the rate of industrial accidents and characteristics, background and safe practices of workers at workplace. This is to enhance safety and health management of workers in small and medium industries in Johor. According to accident reports from the Department of Occupational Safety and Health (DOSH) Johor, data show the staggering increase of the rate of accidents every year. This research is essential in order to avoid, control and reduce the rate of accidents and hence reduce the possibility of industrial accidents occurring among workers. Furthermore, it helps the management to achieve a better safe working procedure for workers. A questionnaire survey, interviews and factory inspection were carried out with questions based on workers’ race, age, education, machines maintenance, general safety, personal protective equipment (PPE) and trainings. The finding of this research shows that relationships exist between the rate of accident and race, education and PPE. No relationships exist between the rate of accident and training, age, machines maintenance and general safety. Further suggestions stressed on the responsible organizations such as DOSH, National Institute of Occupational Safety and Health to take proactive action especially for safety promotion at workplace. The employer should carry out the yearly planning in training as well motivational course to enhance the level of maturity and responsibility among workers. Safety operating procedure should be updated and usage of quality protective equipment may reduce accidents in industries.